Administration and Infrastructure Management in Guidance and Counseling - Thessia Permata Bunda; Neviyarni S; Yarmis Sukur; Pu’ad Maulana; Rahmad Firmansyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to discuss the importance of procuring infrastructure in guidance and counseling to support the successful implementation of guidance and counseling services to ensure the implementation of these services in a cost-effective and efficient manner. This research uses a literature review method that collects various information about guidance and counseling infrastructure facilities from various books, journals and websites as research sources. Infrastructure facilities are needed in the implementation of guidance and counseling services in schools. Because with the infrastructure, counselors can collect data on student needs, process data properly, develop programs according to student needs, store data safely, and carry out services according to student needs obtained from data that has been processed and conduct follow-up on the results of these services, students will feel comfortable and confident when they decide to attend counseling sessions or even just join guidance and counseling groups when there is a comprehensive and well-organized infrastructure.